Cyber Warfare Is The Newest Challenge To Support Indonesian National Resilience - Sholikah, Dwi Imroatus; Harbriyana Putra, Tegar; Fauzan Hidayat , Mohammad (Asian Journal of Social and Humanities, 2024)
Cyber ??operations began to attract attention in international law in the late 1990s, in 1999 the United States Naval War College held the first major legal conference on this issue. In the aftermath of the attacks of September 11, 2001, transnational terrorism and subsequent armed conflict shifted attention from topics to large-scale cyber attacks. Operations occurred in Estonia in 2007 and against Georgia during its war with the Russian Federation in 2008, as well as cyber incidents such as the targeting of Iran's nuclear facilities with the Stuxnet Worm in 2010. Cyber ??warfare is included in organized crime and terrorism as one of the level one threats. The United States National Security Strategy itself calls cyberwarfare one of the most serious national security, public safety and economic challenges that we face as a nation and state. There is a need for clear and concrete international and national legal regulations so that cyber warfare can be prevented and does not cause unnecessary casualties in accordance with the principles of international humanitarian law. Apart from clear regulations, support is needed in the defense sector to form human resources and at the military defense level.